2008
DOI: 10.1080/13602000802548003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Religious Identity Construction among Western-born1 Muslims: Towards a Theoretical Framework

Abstract: The aim of this article is to analyze, on the basis of a particular theoretical approach to identity construction, the factors that shape and help delineate various types of (religious) identity constructions among Western-born generations of Muslims. The author argues that a theoretical framework that combines a socio-cultural use of religion in the construction of group identity with that of scriptural interpretation provides the optimal conceptual tool for not only understanding the formation of religious i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…For Muslims living in Western Europe, acculturation includes not only the negotiation of competing heritage and mainstream host cultural orientations, but also issues of religious diversity within European societies that are historically Christian, highly secularized, and increasingly hostile to the presence of Muslims in Western societies (Duderija, 2008; Güngör, Fleischmann, & Phalet, 2011; Verkuyten, 2007; Verkuyten, Thijs, & Stevens, 2012). Indeed, although immigration and acculturation studies have mostly neglected religious identity dimensions (Sheikh, 2007), a growing number of studies about Muslim immigrants have revealed that Muslim identification and religiosity (practices, beliefs, values) are salient components of daily life for Muslim immigrant communities (Duderija, 2008; Hussain & Bagguley, 2005; Thomas & Sanderson, 2011). The majority of Muslim immigrants in Europe shows high or the highest scores on measures of Muslim identification (Thomas & Sanderson, 2011; Verkuyten, 2007), hence confirming the centrality of this identity dimension and its meaning as an identity marker.…”
Section: Perceived Discrimination Identity and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…For Muslims living in Western Europe, acculturation includes not only the negotiation of competing heritage and mainstream host cultural orientations, but also issues of religious diversity within European societies that are historically Christian, highly secularized, and increasingly hostile to the presence of Muslims in Western societies (Duderija, 2008; Güngör, Fleischmann, & Phalet, 2011; Verkuyten, 2007; Verkuyten, Thijs, & Stevens, 2012). Indeed, although immigration and acculturation studies have mostly neglected religious identity dimensions (Sheikh, 2007), a growing number of studies about Muslim immigrants have revealed that Muslim identification and religiosity (practices, beliefs, values) are salient components of daily life for Muslim immigrant communities (Duderija, 2008; Hussain & Bagguley, 2005; Thomas & Sanderson, 2011). The majority of Muslim immigrants in Europe shows high or the highest scores on measures of Muslim identification (Thomas & Sanderson, 2011; Verkuyten, 2007), hence confirming the centrality of this identity dimension and its meaning as an identity marker.…”
Section: Perceived Discrimination Identity and Well-beingmentioning
confidence: 99%
“…Many authors have also noted that the demarcation between ethnic identity and religion is “blurred”; religious and ethnic identities are positively intertwined for first generations and, even more, for second generation immigrants (Duderija, 2008; Güngör et al, 2011; Maliepaard, Lubbers, & Gijsberts, 2010; Verkuyten & Yildiz, 2007), whereas the relationship between religious and national identification is unclear. Some studies have reported that among Muslim youth residing in Europe, the highest level of religious identification implies a low level of national (host country) identification (Alba, 2005; Crul & Doomernik, 2003; Heim et al, 2011; Maliepaard et al, 2010; Verkuyten et al, 2012; Verkuyten & Yildiz, 2007).…”
Section: Perceived Discrimination Identity and Well-beingmentioning
confidence: 99%
“…While such shifting dynamics of language usage apply to immigrant communities in general, intergenerational transmission of religion, as has already been pointed out, occurs more successfully among Muslims than other UK faith communities. A further finding of the literature on Muslims in the West relates to the decoupling of religion from ethnicity among the second generation (Jacobson 1997;Duderija 2008; DeHanas 2016). Mandaville expresses this clearly:…”
Section: Language As a Window Into Religion Ethnicity And National Cmentioning
confidence: 99%
“…In Belzen’s perspective, it therefore becomes important to design studies that focus on situationally specific beliefs, values, rules, and social interactions as related to individual religious development (Belzen, 1999). This research orientation is of specific importance when studying populations in which religiosity is highly related to cultural traditions, such as the Sunni-Muslim American population (Belzen, 1999; Duderija, 2008). Yet Belzen’s call for the application of cultural psychology to the psychological study of religion, has rarely graduated from the theoretical realm to that of deliberate application in terms of both research design and analysis (Lewis, 2010).…”
Section: Research Contextmentioning
confidence: 99%
“…Furthermore, scholars have argued that Islam becomes a conscious element for Muslims in North America in part due to evolving social interactions related to their religious and cultural minority status (Ahmed, 2009; Daiute & Lucić, 2010; Duderija, 2007; Peek, 2005). Although there have been some notable efforts to begin contextualizing Muslim constructions of religious development within such sociocultural and sociohistorical frameworks, these efforts are often vague and when applied, analyses are frequently unrelated to the complex theoretical paradigms discussed (e.g., Chaudhury & Miller, 2008; Duderija, 2008). In that case, we need to study religious development within an alternative applied framework that incorporates young people’s dynamic and continuing interactions with their everyday environments.…”
mentioning
confidence: 99%